Global perspectives on educational leadership reform the development and preparation of leaders of learning and learners of leadership - Normore, Anthony H. (Advances in educational administration ;, 2010)
The interdependent relationship of leadership and learning for both academics and practitioners is critical for creating innovative leadership practices and partnerships needed for the 21st century schools. Due to the high pressure to demonstrate improvements in student achievement, leadership practices have increasingly resorted to conservative and prescriptive approaches focused more on increasing student achievement scores and less on the artistry of teaching and leading. This book is organized into three sections with four chapters in each section. Section One focuses on the socialization and professional development processes intended to prepare and develop prospective and practicing educational leaders into leadership positions; Section Two examines cultural, political, legal, economic, and social justice issues that affect leaders while serving in the role of educational leader/learner; Section Three encourages "interdisciplinary" educational leaders to re-examine who they are as leaders of learning, as learners of leadership, and life-long learners.